Acting in the best interests of the child: a case study on the consequences of competing child protection legislation in Western Australia - Budiselik, William; Crawford, Frances; Squelch, Joan (Routledge, 2010)
With a focus on the case of CEO, Department for Child Protection v. John Citizen (2007) WASC 312, this article examines the legal issues that the case presents for child-care workers and child welfare organisations when acting in the best interests of a child. This complex case raises a number of issues regarding the issuing of assessment notices (working with children cards), what constitutes the ‘best interests of the child’ and the interplay between potentially conflicting pieces of child welfare and child protection legislation. The first part of the article provides an introduction to the working with children legislation in Western Australia and an overview of the history and facts of the Citizen case. The second part reviews the court's decision, and is followed by a discussion of the consequences of competing legislation that, on the one hand, deemed John Citizen a suitable child carer and, on the other, denied him an assessment notice that would allow him to care for children.